ASPEK MOTIVASI HIDUP DALAM NOVEL “ANAK RANTAU” KARYA AHMAD FUADI - Ike Tri Pebrianti; Meldah Novitasari (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
This study aims to describe the motivational aspects of life in Ahmad Fuadi's novel "Anak Rantau". This study used a descriptive method. The approach used is a literary psychological approach. The data collection techniques used in this study are literature studies. The source of data in this study is the novel "Anak Rantau" by Ahmad Fuadi. The results of the data analysis include aspects of life that occurred in the main character Hepi in overseas. The conclusion of the motivational aspects of life is in the form of (1) The motivational aspect of need for achievement, namely motivation to be liked, motivation to be liked, and motivation to be accepted. (2) The motivational aspects of need for affiliation are motivation to obtain appreciation, motivation to obtain love and belonging. (3) The motivational aspect of need for power is to require power and appear to have an influence on others and the need for a sense of security.